El Excentrico, 1968-03-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
March 20, 1968 [20 de marzo de 1968]. No volume or issue number. Cover has a photo of the hosting committee of the 21st Annual United Food Drive. The talent show took place at Azteca Hall on March 22 from 7 PM to 10 PM. The tardeadas, or social dance, took place on March 24 at the Rainbow Ballroom within the I.E.S. Hall from 2 PM to 10 PM. Admission price for both of these events were a donation of cash or food cans.